Possibility of exploitation of xerophytic crops for the Brazilian semi-arid tropics - Prisco, José Tarquinio (Pesquisa Agropecuaria Brasileira, 2014)
This paper discusses the possibility of domesticating wild xerophytes for the purpose of exploiting them as xerophytic crops in the Brazilian semi-arid tropics. Based on information and knowledge existent in the literature on the morphophysiological mechanisms of drought resistance and their effect on plant productivity, it is demonstrated that wild xerophyte domestication is questionable. Selection and breeding of known crops that already have some drought adaptation mechanism as well as the development of research designed to establish crop, soil and water management practices suitable for the semi-and tropics are recommended.